Electrospun PVDF-based piezoelectric nanofibers: materials, structures, and applications. Issue 4 (1st February 2023) - Zhang, Mengdi; Liu, Chengkun; Li, Boyu; Shen, Yutong; Wang, Hao; Ji, Keyu; Mao, Xue; Wei, Liang; Sun, Runjun; Zhou, Fenglei
Abstract : Effects of filler doping and structural modification on the output properties and the applications of electrospun PVDF-based piezoelectric nanofiber films in the fields of health care, environmental monitoring, and energy collection are reviewed. Abstract : Polyvinylidene fluoride (PVDF) has been considered as a promising piezoelectric material for advanced sensing and energy storage systems because of its high dielectric constant and good electroactive response. Electrospinning is a straightforward, low cost, and scalable technology that can be used to create PVDF-based nanofibers with outstanding piezoelectric characteristics. Herein, we summarize the state-of-the-art progress on the use of filler doping and structural design to enhance the output performance of electrospun PVDF-based piezoelectric fiber films. We divide the fillers into single filler and double fillers and make comments on the effects of various dopant materials on the performance and the underlying mechanism of the PVDF-based piezoelectric fiber film. The effects of highly oriented structures, core–shell structures, and multilayer composite structures on the output properties of PVDF-based piezoelectric nanofibers are discussed in detail. Furthermore, the perspectives and opportunities for PVDF piezoelectric nanofibers in the fields of health care, environmental monitoring, and energy collection are also discussed.